Research on distributed multi-access edge computing based on mimic defense theory - Hongyi ZHU; Xiaoyuan LU; Yi LI (物联网学报)
The highly efficient network resources are provided by multi-access edge computing at the edge of the network,but high security capability is required also due to its distributed position and organization.Based on mimic defense theory,mimic defense structure for distributed multi-access edge computing was proposed.By segmenting data,padding check data and processing data at multiple edge node,dynamic scheduling and decision-making functions according to checksum were implemented.The simulation results show that with the increase of delay cost,the data manipulation and leak rates can be reduced effectively by the proposed structure.The edge node scheduling strategy based on trust and cost is proposed to improve the efficiency and security of the system.